2018
DOI: 10.1007/s10120-018-0825-y
|View full text |Cite
|
Sign up to set email alerts
|

Salvage chemotherapy with the combination of oxaliplatin, leucovorin, and 5-fluorouracil in advanced gastric cancer refractory or intolerant to fluoropyrimidines, platinum, taxanes, and irinotecan

Abstract: Salvage chemotherapy with the combination of oxaliplatin, leucovorin, and 5-fluorouracil has a potential activity and is tolerable for heavily treated AGC with appropriate dose modification and patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Tsuji et al retrospectively reported the efficacy of modified fluorouracil, leucovorin and oxaliplatin (mFOLFOX6) as fourth-or later line treatment in 14 patients who were refractory or intolerant to fluoropyrimidines, cisplatin, taxanes and irinotecan: objective response rate (ORR) of 23.1%, median progressionfree survival (PFS) of 3 months and MST of 8.9 months [16]. Similarly, in the retrospective analysis of 50 patients with similar medical history, Kondoh et al reported that mFOLFOX6 provided ORR of 21.2%, time to treatment failure (TTF) of 2.4 months, and MST of 4.2 months [17]. Thus, oxaliplatin is often used in third-or later line treatment even for patients who have history of platinum administration, and an ORR around 20% has been reported consistently (Table 1) [16][17][18][19][20][21].…”
mentioning
confidence: 98%
“…Tsuji et al retrospectively reported the efficacy of modified fluorouracil, leucovorin and oxaliplatin (mFOLFOX6) as fourth-or later line treatment in 14 patients who were refractory or intolerant to fluoropyrimidines, cisplatin, taxanes and irinotecan: objective response rate (ORR) of 23.1%, median progressionfree survival (PFS) of 3 months and MST of 8.9 months [16]. Similarly, in the retrospective analysis of 50 patients with similar medical history, Kondoh et al reported that mFOLFOX6 provided ORR of 21.2%, time to treatment failure (TTF) of 2.4 months, and MST of 4.2 months [17]. Thus, oxaliplatin is often used in third-or later line treatment even for patients who have history of platinum administration, and an ORR around 20% has been reported consistently (Table 1) [16][17][18][19][20][21].…”
mentioning
confidence: 98%
“…Tsuji et al retrospectively reported the efficacy of modified fluorouracil, leucovorin and oxaliplatin (mFOLFOX6) as fourth- or later line treatment in 14 patients who were refractory or intolerant to fluoropyrimidines, cisplatin, taxanes and irinotecan: objective response rate (ORR) of 23.1%, median progression-free survival (PFS) of 3 months and MST of 8.9 months [ 16 ]. Similarly, in the retrospective analysis of 50 patients with similar medical history, Kondoh et al reported that mFOLFOX6 provided ORR of 21.2%, time to treatment failure (TTF) of 2.4 months, and MST of 4.2 months [ 17 ]. Thus, oxaliplatin is often used in third- or later line treatment even for patients who have history of platinum administration, and an ORR around 20% has been reported consistently ( Table 1 ) [ 16–21 ].…”
Section: Background and Rationalementioning
confidence: 99%
“…It has a high incidence in Eastern Asia, including Ja-Oncology 2021;99:632-640 DOI: 10.1159/000517344 pan, and its occurrence is particularly common in male individuals [2]. Cytotoxic chemotherapy and targeted molecular therapy have been developed and applied for unresectable and recurrent gastric cancer and have contributed to improved prognosis [3]. However, sufficient therapeutic effects cannot be obtained with these approaches alone, and immune checkpoint inhibitors (ICIs) were thus introduced.…”
Section: Introductionmentioning
confidence: 99%